Conceptual foundations of organizational structure: re-structuring of women's health services. Issue 3 (14th December 2021) - Nugus, Peter; Travaglia, Joanne; MacGinley, Maureen; Colliver, Deborah; Mazaniello-Chezol, Maud; Claudio, Fernanda; Lewis, Lerona Dana
Abstract : Purpose: Researchers often debate health service structure. Understanding of the practical implications of this debate is often limited by researchers' neglect to integrate participants' views on structural options with discourses those views represent. As a case study, this paper aims to discern the extent to which and how conceptual underpinnings of stakeholder views on women's health contextualize different positions in the debate over the ideal structure of health services. Design/methodology/approach: The researchers chose a self-standing, comprehensive women's health service facing the prospect of being dispersed into "mainstream" health services. The researchers gathered perspectives of 53 professional and consumer stakeholders in ten focus groups and seven semi-structured interviews, analyzed through inductive thematic analysis. Findings: "Women's marginalization" was the core theme of the debate over structure. The authors found clear patterns between views on the function of women's health services, women's health needs, ideal client group, ideal health service structure and particular feminist discourses. The desire to re-organize services into separate mainstream units reflected a liberal feminist discourse, conceiving marginalization as explicit demonstration of its effects, such as domestic abuse. The desire to maintain a comprehensive women's health service variously reflected post-structural feminism's emphasis on plurality of identities, and a radical feminist discourse, holding that womanhood itself constituted a category of marginalization – that is, merely being at risk of unmet health needs. Originality/value: As a contribution to health organizational theory, the paper shows that the discernment of discursive underpinnings of particular stakeholder views can clarify options for the structure of health services.